2005
DOI: 10.1539/joh.47.149
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Menstrual Function and Life Style/Working Conditions among Nurses in Taiwan

Abstract: -This study was aimed at understanding the relationship among menstrual pattern, dysmenorrhea, life style and working conditions in nurses. The nurses were randomly selected from a medical center in Northern Taiwan. Each subject completed daily records including life and working conditions during the study period. The study showed that there were statistically significant differences in work years, daily working hours and type of work shift among nurses that worked at different units in the hospital. In the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 17 publications
5
92
1
6
Order By: Relevance
“…Three-quarters of the nurses in our investigation reported having regular menstrual cycles, which is slightly higher than a previous study of Taiwanese nurses 38) where 35% had irregular menstrual cycles, although it was similar to another Taiwanese investigation 26) where 84% had an average menstrual cycle length of between 24 and 35 d. The average cycle length of Japanese nurses (around 30 d) was higher than the aforementioned study of Taiwanese nurses (average 26 d) 38) , although the bleeding time was similar between Japan and Taiwan (5.9 versus 5.8 d, respectively) 38) . Length of menstrual cycle among nurses is known to be influenced by various issues, including occupational factors, with one study 39) finding correlations between working in high stress units and long, monophasic cycles among American nurses.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Three-quarters of the nurses in our investigation reported having regular menstrual cycles, which is slightly higher than a previous study of Taiwanese nurses 38) where 35% had irregular menstrual cycles, although it was similar to another Taiwanese investigation 26) where 84% had an average menstrual cycle length of between 24 and 35 d. The average cycle length of Japanese nurses (around 30 d) was higher than the aforementioned study of Taiwanese nurses (average 26 d) 38) , although the bleeding time was similar between Japan and Taiwan (5.9 versus 5.8 d, respectively) 38) . Length of menstrual cycle among nurses is known to be influenced by various issues, including occupational factors, with one study 39) finding correlations between working in high stress units and long, monophasic cycles among American nurses.…”
Section: Discussioncontrasting
confidence: 81%
“…Dysmenorrhoea was very common among the Japanese nurses in our study, with almost half experiencing it constantly. Around 30% of nurses in a previous Taiwanese study reported always suffering from dysmenorrhoea 38) , whereas the prevalence was approximately 35% among their Korean counterparts 27) . In other parts of Asia, studies of Chinese nurses have been somewhat contradictory, with one study reporting a similar rate of dysmenorrhoea to ours 25) , although in another investigation 28) , the rate was much lower (14%).…”
Section: Discussionmentioning
confidence: 95%
“…[6][7][8][9][10] Several studies have examined the relation between shift work and menstrual cycle patterns, [11][12][13][14][15][16] three of which were studies of nurses. [11][12][13] While most of these studies reported an association of shift work with menstrual cycle perturbations, four had small sample sizes (ranging from 12 to 151 participants), thereby limiting their ability to adjust for confounding factors. 12,13,15 One study examined 479 Canadian poultry workers who reported day-to-day variability in work schedule (defined as the day of work beginning at irregular or unpredictable times).…”
Section: Discussionmentioning
confidence: 99%
“…Unsuitable, demonstrably ineffective or harmful methods: magnetic therapy, osteopathy, manual therapy, avoidance of coffee, cola and/or alcohol, homoeopathy, and relaxation therapy [80][81][82][83][84][85]. Possibly useful methods: traditional Chinese herbal medicine, acupuncture and acupressure, moxibustion, omega-3 fatty acids, vitamin B1, vitamin E, magnesium, exercise, yoga, chaste tree, yarrow, toki-shakuyaku-san -Kampo medicine from Japan, cinnamon [81,[86][87][88][89][90][91][92][93][94][95].…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%